Обгрунтування форми мікроводоростевих установок - Голодний, І. М. (Енергетика і автоматика, 2017)
THE SUBSTANTIATION OF THE MICROWATER EQUIPMENT FORMI. Golodnyi Introduction. Widely studied in biological experiments and industrial cultivation of a highly algae such as spirulina and chlorella. Chlorella contains 50...5% (70% spirulina) protein, 30…35% carbohydrates, 7...10% fat, a unique set of amino acids and vitamins. They are used as feed and food additives. Growing algae easily controlled. When creating the necessary conditions, they can be cultivated year-round, getting constantly biomass crops.Analysis of recent research and publications. For the cultivation of microalgae There are two kinds - open and closed. Open the settings are divided into deep and not deep. Installation depth with form pool or bath of any form. The depth of the layer in which 0,25...0,30 m, stirring bubbling slurry, pumps, mixers. Nehlybynni settings are shaped chutes, cascades, shallow baths. The depth of the layer of slurry 0,05...0,25 m. Disadvantages outdoor installations: large acreage units, small density slurry, it is likely to be infected culture, higher costs of carbon dioxide. Closed cultivation installations isolated from the environment. They are mounted on plastic pipes placed horizontally or vertically and closed in a ring, thus enhancing productivity (mainly due to more efficient use of CO2 by 20%), reduce pollution cultures by 30% and water loss by evaporation.In this paper the process of growing microalgae on exposure conditions effective suspension, based on which a theoretical study of the most appropriate form of lighting installation surface.Purpose - improving the cultivation of algae.Methods. In studies used the theory of absorption of light energy algal suspensions.Results. The effectiveness of the settings defined microalgae important criteria such as growth rate and energy efficiency of photosynthetic cell culture, which are determining factors: light, CO2 concentration and minerals in a nutrient medium, temperature and stirring suspension. Photosynthesis and growth of algae is mainly limited by light energy and carbon dioxide concentration in the culture medium. The absorption of light energy chlorella suspension is subject to the laws of Bouguer-Lemberta-Beyer. Which shows that the irradiated surface at a constant increase in the rate of growth achieved by decreasing the thickness of the layer deterioration. Extreme case is the separation of the suspension endless endless number of thin layers. From which it follows that the same illumination performance unit ball 6 times, and the cylinder is 4 times greater than the basic layer. In fact these ratios for a flat, cylindrical and spherical plants have lower values. This is due to the exponential dependence of the absorption of light energy.Conclusions. Theoretical studies found that the same basic illumination performance ball 6 times, and the cylinder is 4 times greater than the basic layer.The closest analogue for plants growing algae with a spherical surface as effectively be setup division suspension to drops in the form of rain, where drops in free fall take the form of small balls, while lighted.